2005
DOI: 10.1037/0893-164x.19.4.433
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nicotine on Attention and Working Memory in Never-Smokers.

Abstract: The subjective and physiological effects of nicotine in nicotine-naive individuals are consistent across studies, though the cognitive effects are variable: Positive, negative, or no effects have been reported. Assessing specific cognitive processes (e.g., alerting, orienting, executive function, and phonological and visuospatial working memory) may help reduce this variability. This within-subject study (N = 20) was designed to assess the effect of nicotine gum (0, 2, or 4 mg) on subjective, physiological, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 44 publications
5
44
0
Order By: Relevance
“…Although several studies have demonstrated that smoking or nicotine can improve working memory in tobacco-deprived or nondeprived smokers (Ernst et al, 2001;Grobe et al, 1998) and in nonsmokers (Kumari et al, 2003;McClernon et al, 2003), our results are in agreement with others who reported no nicotine-associated improvement in working memory (Kleykamp et al, 2005;Myers et al, 2004;Park et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although several studies have demonstrated that smoking or nicotine can improve working memory in tobacco-deprived or nondeprived smokers (Ernst et al, 2001;Grobe et al, 1998) and in nonsmokers (Kumari et al, 2003;McClernon et al, 2003), our results are in agreement with others who reported no nicotine-associated improvement in working memory (Kleykamp et al, 2005;Myers et al, 2004;Park et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies reported enhanced working memory following nicotine administration to nonsmokers (Foulds et al, 1996;Kumari et al, 2003;McClernon et al, 2003) and former smokers and abstinent smokers (Ernst et al, 2001). In contrast, other studies reported that nicotine either had no effect (Heishman et al, 1993;Kleykamp et al, 2005;Myers et al, 2004) or impaired working memory (Park et al, 2000). Heishman and Henningfield (2000) found that nicotine gum enhanced speed, but decreased working memory accuracy in nonsmokers.…”
Section: Introductionmentioning
confidence: 94%
“…Only N-back reaction time was influenced by nicotine, an effect that is consistent with previous findings of nicotine-induced enhancement. 38,43 However, other work has shown that nicotine has no effect on cognition in this population 28,42 or even produces impairment, 41,44 suggesting further exploration of the specific cognitive processes responsive to nicotine. 42 The moderate caffeine doses used in this study did not influence either physiological or subjective response.…”
Section: Discussionmentioning
confidence: 99%
“…38,43 However, other work has shown that nicotine has no effect on cognition in this population 28,42 or even produces impairment, 41,44 suggesting further exploration of the specific cognitive processes responsive to nicotine. 42 The moderate caffeine doses used in this study did not influence either physiological or subjective response. Although these results seem to contradict some previous work, 6,9 the higher doses used in those studies (up to 4 times greater than the 150 mg dose used in this study) may account for the discrepancy (but see also 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine administration facilitates orienting and alerting aspects of attention (Levin et al, 1998;Witte et al, 1997). Nicotine administration may also facilitate memory function (e.g., Perkins et al, 1994), although there are also reports that it may have no effect or even impair memory (e.g., Kleykamp et al, 2005). Inconsistent results such as these suggest that a variety of variables can modulate the cognitive effects of nicotine.…”
Section: Introductionmentioning
confidence: 79%